Determination of nuclear materials' elemental compistion for the needs of nuclear forensics; Методология проектирования молодежного научно-инновационного пространства как основа подготовки современного инженера - Dolmatov D. O. (Integrity of traditions and innovations as the basis for the development of modern engineering science, 2014)
Заглавие с экрана